Reduction in D-dimer levels after treatment with Auxora in patients with severe COVID-19 pneumonia - Peter C. Hou; Joseph Miller; Charles Bruen; Fady Youssef; Michael J. Schnaus; Kathyrn Brouillette; Raul Mendoza-Ayala; Jeffrey Zhang; Kenneth Stauderman; Sudarshan Hebbar (Thrombosis Update, 2025)
Introduction: A phase 2 double-blinded trial (CARDEA) (NCT04345614) in patients diagnosed with COVID-19 revealed that intravenous zegocractin treatment (Auxora™) was associated with improved clinical outcomes compared to standard of care (SOC). D-dimer serum level is a biomarker of thrombosis in COVID-19, and elevated levels are directly correlated with a high risk of poor outcomes. Here, we report biomarker analyses from blood samples collected from patients in that study. Methods: Quantification of D-dimer levels was the primary endpoint of the study. Secondary endpoints measured levels of angiopoietin 1 (Ang1), angiopoietin 2 (Ang2), soluble CD25 (sCD25), and renin. CARDEA was conducted in 17 U S. clinical centers. Patients were randomly assigned to receive Auxora plus SOC (n = 143) or placebo plus SOC (n = 141). The medications were administered by a 4-h intravenous infusion at 2.0 mg/kg (1.25 mL/kg) at 0-h and 1.6 mg/kg (1 mL/kg) at 24 h and 48 h. Findings: Patients in the Auxora group had a baseline mean D-dimer value of 2.61 mg/L and those in the placebo group had a value of 2.05 mg/L. Treatment with Auxora resulted in a statistically significant decrease in D-dimer levels within the first 72 h compared to placebo (delta = −0.92; [95 % CI: −1.82, −0.02]; p < 0.046). The decrease in D-dimer levels correlated with an increase in imputed PaO2/FiO2 at 72 h (r: −0.193; p < 0.05) and improved clinical status at 168 h (r: 0.218, p < 0.01). Auxora treatment reduced levels of Ang2 and sCD25, and increased Ang1 levels compared to placebo. Conclusion: Auxora treatment significantly reduced D-dimer levels in patients diagnosed with COVID-19, and the decrease was associated with an improved clinical status.